2020
DOI: 10.1371/journal.pone.0231253
|View full text |Cite
|
Sign up to set email alerts
|

Association between boarding in the emergency department and in-hospital mortality: A systematic review

Abstract: ImportanceBoarding in the emergency department (ED) is a critical indicator of quality of care for hospitals. It is defined as the time between the admission decision and departure from the ED. As a result of boarding, patients stay in the ED until inpatient beds are available; moreover, boarding is associated with various adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 55 publications
1
53
1
3
Order By: Relevance
“…Previous investigations have addressed the question of whether ED crowding affects the mortality and morbidity rates in the ED. Moreover, several studies and systematic reviews have confirmed the association between ED crowding and increased mortality rates [9][10][11][12][13][14][15][16]. However, the effects of crowding on the quality of care were not examined in this study.…”
Section: Possible Crowding Responsesmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous investigations have addressed the question of whether ED crowding affects the mortality and morbidity rates in the ED. Moreover, several studies and systematic reviews have confirmed the association between ED crowding and increased mortality rates [9][10][11][12][13][14][15][16]. However, the effects of crowding on the quality of care were not examined in this study.…”
Section: Possible Crowding Responsesmentioning
confidence: 82%
“…Elderly patients are at a higher risk than younger patients for complications related to hospitalization and long stays in the ED. Several international studies have reported that overcrowding can result in a greater number of adverse events, with increased morbidity and mortality, prolonged LOS, and reduced healthcare quality [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowding can lead to poor adherence to approved guidelines [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Overcrowding can also lead to patients’ poor outcomes, adverse events, increased morbidity and mortality, and overall inferior health care [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Often, crowding is due to access block, which has been defined as a delay in bringing admitted patients to the inpatient beds at the wards [ 52 , 71 , 72 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis exploring ED boarding and in-hospital mortality revealed a weak trend toward this association driven by positive associations in half of the included studies. 13 None of the included studies demonstrated the reverse. The implications for the care of the ED patient are that timeliness, or lack thereof, can lead to measurable gains or losses in mortality.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, we identified a longer length of stay for admitted patients, likely accounted for by an increased time of ED boarding. A recent meta‐analysis exploring ED boarding and in‐hospital mortality revealed a weak trend toward this association driven by positive associations in half of the included studies 13 . None of the included studies demonstrated the reverse.…”
Section: Discussionmentioning
confidence: 98%